Cystic lymphangioma of the elbow in an infant: A case report - N. Merouane; A. El Bakkaly; R. Nang; Y. Lahraoui; A. Amrani; A. Dendane; Z.F. Alami; T. El Madhi (Elsevier, 2018)
The macrocystic Lymphatic malformations are located in the neck in 75% and axilla in 20% of cases. Involvement of the upper limb and particularly the elbow is very rare. We report on a case of macrocystic lymphatic malformation localized at the elbow. It was a 18 month old infant. Was followed up in our department since the age of 6 months because of congenital subcutaneous soft, painless mass of the right elbow. Ultrasonography and the magnetic resonance imaging (MRI) were evocative of the diagnosis of macrocystic lymphatic malformation. Surgical resection was complete without postoperative recurrence. MRI is useful for the diagnosis and the definition of tumor limits. The Treatment is difficult because of their location and rough delimitation. Keywords: Macrocystic lymphangioma, Elbow, Surgery